Teoretična in vsebinska zasnova trajnostno sonaravnega napredka - Plut, Dušan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2005)
Implementation of the principles of sustainability in the economic, social and environmental field means that organisation and (material) operation of a society is permanently adapted to the environment. Sustainable close-to-naturemanaged development, or in a broader sense progress, means permanent (sustainable) and simultaneous improvement of material, social and environmental quality of life, thus a permanent raise of the welfare in its broader sense of all inhabitants within the capacities (limitations) of the environment. The opportunity of geography is to take an active part in the realisation of close-to-nature managed patterns of the spatial organisation of human activity.
Keywords: natural environment; okolje; ecology; ekologija; pokrajinska ekologija; sonaravni razvoj; sustainable development; trajnostni razvoj; družbeni razvoj; ekonomski razvoj